Comparison and analysis of the speed changes of the top three men's 20km men walking in the 2018 World Championships - Li, X.; Qin, J.-J.; Hu, G.-S.; Sun, J. N.; Ding, H.-T.; Yan, N.; Wang, Z. (DEStech Transactions on Social Science, Education and Human Science, 2020)
The walking race is the track and field event that has won the most Olympic and world championships in China. Race walking is a technology-led endurance event. Because the walking race is judged solely by the referee's eyes, the athlete's skills are very important. Once fouls are sent off, many years of hard training will disappear. This paper uses research methods such as literature data method, mathematical statistics method, and comparative analysis method. The purpose is to study and analyze the changes in the competition speed of the top three athletes of the men`s 20km race in the 2018 Asian Games in Jakarta. The gap between them is improved, thereby improving the overall level of our male 20km race walking athletes. The research shows that the speed of Chinese athlete Kaihua Wang in the first half is relatively fast and stable compared with the speed of the other two athletes. This is where Kaihua Wang's strengths lie, and also where he needs to continue to play in future training and competition. In the 20km race walking competition of Chinese athlete Kaihua Wang, the speed change in the second half was relatively large compared with the speed in the first half, and there was a sprint speed performance in the second half. However, compared to champion Japanese athlete Ikeda Xiangxi, the speed was not strong enough. In the 20km race walking competition of Chinese athlete Kaihua Wang, from the analysis of speed changes throughout the race, they are all slow-forward and fast-forward athletes. However, from the results of the entire competition, it was shown that the performance of the three athletes did not reach their personal best, all of which were affected by the environment and other factors.